2003
DOI: 10.3759/tropics.12.85
|View full text |Cite
|
Sign up to set email alerts
|

Forest Structure and Tree Species Diversity along an Altitudinal Gradient in Doi Inthanon National Park, Northern Thailand

Abstract: A study on forest vegetation along an altitudinal gradient was conducted in Doi Inthanon National Park, Chiangmai, Thailand. The purpose of the study was to elucidate how community characteristics change from lowland to mountain vegetation in the tropical monsoon climatic zone in mainland Southeast Asia by using floristic composition and species abundance data collected from forty five plots at different altitudes and forest types.Community classification by cluster analysis suggested 45 sample stands to be cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The rainfall profiles indicate that in March there is almost the same rainfall quantity at all altitudes, but the same cannot be said for temperature (Teejuntuk et al . ). Precipitation is a constant abiotic factor along the elevational gradient, at this specific time of year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rainfall profiles indicate that in March there is almost the same rainfall quantity at all altitudes, but the same cannot be said for temperature (Teejuntuk et al . ). Precipitation is a constant abiotic factor along the elevational gradient, at this specific time of year.…”
Section: Discussionmentioning
confidence: 99%
“…A strong seasonality is observed on Doi Inthanon: a dry season from December to March (no rainfall, an average of 20°C at low elevations and 10°C at high elevations), and a wet season from April to November (extensive rainfall particularly at high elevations, 25°C at low elevations, 10–15°C at summit) (Bedos , Teejuntuk et al . , Plant et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The montane zone is further divided into lower and upper montane forests at approximately 1800 m asl (Santisuk 1988). Tree species diversity increases with elevation up to around 1800 m, and then decreases toward the summit (Teejuntuk et al 2002).…”
Section: Study Site and Permanent Plotmentioning
confidence: 99%
“…This result showed that the altitudinal zone was one of the main effects on the variation in Araceae species. Many researches reported about the effect of altitudinal gradients factor could determine the distribution of many plant families in Doi Inthanon National Park [30,31] and Doi Suthep-Pui National Park [32,33]. In South Korea on the ridge of the Baekdudaegan Mountains [34] and in China at Gauncen Mountain [35], the latitude and altitude had effects on plant species richness, diversity and community and different species were also found in Malaysia [36] and Brazil [37].…”
Section: Compared Species To Doi Inthanon National Parkmentioning
confidence: 99%